A critical-discursive analysis about female empowerment in the song “I am my problem” in the light of Rildo Cosson’s didatic sequence (Research, Society and Development, 2021)
Female empowerment, something that women have been fighting for a long time, is something that unfortunately does not happen in the same proportion of the efforts undertaken by them. Even though women have stood out in society for a long time, after a lot of struggle, occupying spaces previously destined exclusively to the male audience, there are still women's difficulties in consolidating their independence and in achieving equal rights between genders, which ends up empowering women to continue in the struggle. Thus, this article aims to analyze, under a critical-discursive bias, the female empowerment in the song I am my problem, by Clarice Falcão, to suggest, from this analysis, a didactic sequence proposal to Portuguese Language Teachers of Elementary School, specifically from the 9th grade, with the aforementioned theme. This is a bibliographic research, based on a literature review, analyzed from a theoretical framework appropriate to the topic in question. As a result of the analysis, we realized that, although there are still traces of male and female behavior in a patriarchal and sexist society, women have found their place in society and have raised the banner of empowerment, showing men that they are free and know their place in society. Thus, we conclude that the struggle for female empowerment is something that must be strengthened every day and that women need to unite even more in order to strengthen this struggle.